Modern diesel technology : heating, ventilation, air conditioning, & refrigeration - Dixon, John (John Charles), 1963-; National Automotive Technicians Education Foundation (Clifton Park, NY : Delmar Cengage Learning, 2014)
Detailing the foundations of truck heating, air conditioning, engine cooling, and truck-trailer refrigeration, this book integrates modern technical terms with photos that demonstrate typical, on-the-job tasks in logical sequence. It delivers technical accuracy and depth of HVAC/R information you need for a rewarding career as a diesel technician.
Heating, ventilation, and air conditioning -- Environmental and safety practices -- Thermodynamics -- Air-conditioning components: compressor, condenser, and receiver-drier -- Air-conditioning components: metering devices, evaporator, accumulator -- Refrigeration system -- Service procedures -- Truck engine cooling systems -- Cab climate control supplemental truck heating and cooling -- Troubleshooting and performance testing -- APAD/ACPU A/C control systems -- Coach air conditioning -- Truck-trailer refrigeration equipment -- Refrigeration components -- Refrigerant flow control -- Truck-trailer refrigeration electrical components -- Truck and trailer refrigeration maintenance.
Includes index.
Keywords: Diesel trucks -- Heating and ventilation; Diesel trucks -- Air conditioning; Diesel trucks -- Air conditioning